Village Tourism Innovation Based on Cultural Immersion and Eco-Tourism to Increase Village Original Income: A Literature Study in the East Kalimantan Context - Dhanny septimawan sutopo (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2026)
Objective: To explore rural tourism innovation through cultural immersion and eco-tourism approaches as a strategy to increase villages' original income in Indonesia, with a specific focus on the East Kalimantan context. Design/Methods/Approach: This study uses a descriptive qualitative method with a library research approach to analyze the implementation of culture- and environment-based tourism concepts within sustainable rural development. Findings: The integration of cultural immersion and eco-tourism can significantly increase villages' original income by 40–60% through tourism product diversification, local community empowerment, and the preservation of cultural and environmental assets. Furthermore, the study formulates a rural tourism innovation model comprising four main components: the development of authentic tourism products, local community empowerment, environmental conservation, and the digitalization of promotion. Originality/Value: This study provides a novel contribution by formulating an integrated rural tourism innovation model that combines cultural and ecological aspects specifically tailored for the East Kalimantan region, complemented by a concrete projection of the percentage increase in villages' original income, which has not been extensively mapped in previous literature. Practical/Policy implication: This rural tourism model can be adopted by policymakers and local governments as a strategic guide in designing regulations for sustainable tourism village development, optimizing the diversification of village income sources, and serving as a reference for local human resource capacity-building programs in East Kalimantan.